Energy analysis of air conditioning system using PID and Fuzzy logic controllers [compact disc] - Henry Nasution 252751 (2006)
Thesis (Doktor Falsafah (Fakulti Kejuteraan Mekanikal)) - Universiti Teknologi Malaysia, 2006